2017
DOI: 10.21608/zvjz.2017.7887
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Biochemical Studies on some Antimicrobials in Clarias garipeinus Fish Infected with Aeromonas hydrophila

Abstract: The present study was carried out to investigate the efficacy of propolis and norfloxacin against Aeromonas hydrophila in Nile catfish (Clarias garipeinus). Fish were collected from a private fish farm in Sharkia Governorate and fed commercial fish diet. Fish were divided into six groups; Group 1: non-infected non-treated, Group 2: experimentally infected with A. hydrophila and non-treated, Group 3: normal fish administered propolis in feed by dose (10g/kg BW for 10 days), Group 4: infected fish treated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…In the present study, the infected non-treated group showed a significant increase in transaminase activities, urea and creatinine. similar results obtained by Amer et al (2009) andEl Alem et al (2017). The groups supplemented with B. subtilis revealed improvement in transaminase activities and kidney function.…”
Section: Bsupporting
confidence: 90%
“…In the present study, the infected non-treated group showed a significant increase in transaminase activities, urea and creatinine. similar results obtained by Amer et al (2009) andEl Alem et al (2017). The groups supplemented with B. subtilis revealed improvement in transaminase activities and kidney function.…”
Section: Bsupporting
confidence: 90%